2008
DOI: 10.4176/080322
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Penetrating Injury of the Diaphragm: An Experience from a District Hospital

Abstract: In this study we review our experience in using laparoscopy as a diagnostic and therapeutic tool in dealing with penetrating diaphragmatic injuries due to stab wounds and look at the feasibility of using this procedure in other similar institutions. Thirty patients, all of whom were males 20-30 years of age, presented to the surgical emergency unit of our hospital with upper abdominal and lower chest wall stab wounds between 01-05-1998 and 30-11-2006. Diagnosis of the diaphragm injury was either obvious with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…In many studies in the literature, shorter hospital stay has been reported in the laparoscopic approach than in the open approach. [13,14] In our series, male patients were significantly higher, in accordance with the literature. Our mean age was 47.25+12.9 and mean hospitalization time was 7.5+3.8 days.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In many studies in the literature, shorter hospital stay has been reported in the laparoscopic approach than in the open approach. [13,14] In our series, male patients were significantly higher, in accordance with the literature. Our mean age was 47.25+12.9 and mean hospitalization time was 7.5+3.8 days.…”
Section: Discussionsupporting
confidence: 92%
“…When patients with multiple traumas were evaluated, the incidence of diaphragmatic injury was 3% (0.8%-5.2%). [14] 75% of the diaphragmatic ruptures are due to blunt traumas and 25% are due to penetrating traumas. [15] Because the left medial posterolateral tendomuscular area of the diaphragm is the weakest region of the diaphragm in embryological development, rupture is more common on the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy can illuminate both hemidiaphragms to rule out diaphragmatic rupture and can also identify other injuries in the abdominal cavity. Open surgical approaches in contrary to laparoscopic repair is associated with increased postoperative pain, increased duration of hospital stay and development of long term complications like incisional hernia [7] , [8] . Most surgeons concur that diaphragmatic injuries are amenable to laparoscopic repair in carefully selected patients under the stipulation that the operating surgeon has a high degree of expertise and skill.…”
Section: Discussionmentioning
confidence: 99%
“…Repair of diaphragmatic rupture has been performed through a laparotomy or a thoracotomy incision for many years. However, open surgical procedures are associated with increased postoperative pain, increased hospital length of stay, and development of long-term complications, such as an incisional hernia [ 9 , 10 ]. In comparison, laparoscopy offers the benefits of less postoperative pain (and thus less dependence on analgesics), faster recovery, and a decreased risk of wound complications [ 2 , 11 ].…”
Section: Discussionmentioning
confidence: 99%